Changes in the prevalence of three disease-causing pathogens in bird-borne blacklegged ticks: Borrelia burgdorferi sensu stricto, Anaplasma phagocytophilum, and Babesia microti - Medha Pandey; J. Alan Clark; Nicholas P. Piedmonte; Christine P. Zolnik; Justin R. Pool; Thomas J. Daniels; Evon Hekkala (Ticks and Tick-Borne Diseases)
Borrelia burgdorferi sensu stricto, Anaplasma phagocytophilum, and Babesia microti are common tick-borne pathogens of medical and veterinary concern in the United States and are transmitted by the blacklegged tick (Ixodes scapularis). The range expansion of ticks and their pathogens depends on the movements of vertebrate hosts, including birds. Flight grants birds high mobility – giving them the potential to rapidly expand the range of ticks and their pathogens, thus impacting human, wildlife, and livestock risk of exposure to tick-borne diseases. We examined the prevalence of B. burgdorferi sensu stricto, A. phagocytophilum, and Ba. microti in bird-borne I. scapularis larvae over the last decade and the relative importance of specific bird species in their maintenance in the environment. Engorged I. scapularis larvae collected from birds in 2010 and 2019 were tested for pathogens using qPCR. Annual prevalences of B. burgdorferi sensu stricto, A. phagocytophilum, and Ba. microti significantly differed between years (P < 0.05), changing from 17.2 %, 9.7 %, and 0 % in 2010 to 33.8 %, 2.9 %, and 5.1 % in 2019, respectively. Bird species significantly predicted B. burgdorferi sensu stricto infection with the American robin (Turdus migratorius), Carolina wren (Thryothorus ludovicianus), and northern house wren (Troglodytes aedon) yielding ticks with high infection prevalences. Migratory and resident bird species may play important roles in the environmental maintenance of tick-borne pathogens and their range expansion in various ways, and further assessments of these pathogen-vector-host interactions are needed.